Legal Analysis of Acts of Embezzlement in the Family (Study of Decision Number Number 1314 / Pid.B / 2024 / PN Mdn) - Hasbi Simanjuntak, Mhd; Hakim Lubis, Andi; Hakim, Lukman; Martha Sasea, Enny (International Asia Of Law and Money Laundering, 2024)
This study aims to look criminologically and juridically about crime in human action which compromises the basic norms of society. Actions elements that violate the rules of living and growing in the community. The type of research used is descriptive analytical about juridical normative, the main material in this study is secondary data conducted by collecting materials in the form of : Primary legal materials, namely legal materials in the form of legislation, official documents have authority related to the problem, namely the Criminal Code. Secondary legal materials, namely all materials laws that are the publication of unofficial documents include books, scientific works. Tertiary Law Materials, that is, the material that provides and explanation of the primary legal material and secondary legal material, such as general dictionaries, legal dictionaries, scientific journals, magazines, newspapers and the internet are still relevant to this study, the results of research and discussion to explain the elements of the crime of embezzlement applied in Decision No. 1314 / Pid.B / 2024 / PN Mdn consists of elements of a subjective offense in the form of a deliberate violator in order to embezzle someone else's property as defined in this article of the law through the wording: intentional and objective violation element it consists of: anyone element, unlawfully mastered element, object element, partial or complete element owned by others and the element of the object there is not for evil.